Cancer: improving early detection and prevention. A community practice randomised trial. Issue 6828 (14th March 1992) - Dietrich, A. J.; O'Connor, G. T.; Keller, A.; Carney, P. A.; Levy, D.; Whaley, F. S.
Abstract : OBJECTIVE–To test the impact of physician education and facilitator assisted office system interventions on cancer early detection and preventive services. DESIGN–A randomised trial of two interventions alone and in combination. SETTING AND SUBJECTS–Physicians in 98 ambulatory care practices in the United States. INTERVENTIONS–The education intervention consisted of a day long physician meeting directed at improving knowledge, attitudes, and skills relevant to cancer prevention and early detection. The office system intervention consisted of assistance from a project facilitator in establishing routines for providing needed services. These routines included division of responsibilities for providing services among physicians and their staff and the use of medical record flow sheets. MAIN OUTCOME MEASURES–The proportions of patients provided the cancer prevention and early detection services indicated annually according to the US National Cancer Institute. RESULTS–Based on cross sectional patient surveys, the office system intervention was associated with an increase in mammography, the recommendation to do breast self examination, clinical breast examination, faecal occult blood testing, advice to quit smoking, and the recommendation to decrease dietary fat. Education was associated only with an increase in mammography. Record review for a patient cohort confirmed cross sectional survey findings regarding the office system for mammography and faecal occult blood testing. CONCLUSION–Community practices assisted by a facilitator in the development and implementation of an office system can substantially improve provision of cancer early detection and preventive services.